Bacterioplankton Richness and Composition in a Seasonal Urban River - Xiao, Zufei; Li, Gang; Zhao, Yi; Xiao, Keqing; Chen, Qinglin; Bao, Peng; Tang, Jianfeng; Ruan, Tian; Zama, Eric Fru; Xu, Yaoyang (Frontiers in Environmental Science, 2021)
Urbanization and seasonality strongly influence the bacterial composition of the soil. However, aquatic environments such as rivers are understudied owing to their high dynamics and therefore rules relating to more static habitats such as lentic or terrestrial environments may be limited. Here, we compared the spatio-temporal patterns of bacterioplankton communities in Zhangxi river along a gradient of urbanization using 16S ribosomal DNA (rDNA) identification. The alpha and beta diversity of bacterioplankton showed no a significant response to watershed urbanization. A significant difference in predicted functional proﬁles of the bacterioplankton community was also revealed between the wet and dry season. The bacterioplankton community assembly was driven by both deterministic and stochastic processes. Stochasticity was one of the most vital processes affecting the bacterioplankton communities in both wet and dry seasons, explaining over 50% variation in the community by null model analysis. Bacterioplankton co-occurrence patterns in the river changed with the seasons. More notably, the composition of bacterioplankton communities was inconsistent with the alternations of the spatial distance offering meaningful implications for the interactions between Zero-radius operational taxonomic units (ZOTUs) and the dynamics of bacterioplankton communities in surface water. In summary, we found clear patterns of seasonal variations in the bacterioplankton community structures.